A study of history - Toynbee, Arnold (Oxford University Press, 1957)
Arnold Toynbee's A Study of History has been acknowledged as one of the greatest achievements of modern scholarship. A ten-volume analysis of the rise and fall of human civilizations, it is a work of breath-taking breadth and vision. D.C. Somervell's abridgement, in two volumes, of this magnificent enterprise, preserves the method, atmosphere, texture, and, in many instances, the very words of the original. Originally published in 1947 and 1957, these two volumes are themselves a great historical achievement. Volume 1, which abridges the first six volumes of Toynbee's study, includes the Introduction, The Geneses of Civilizations, and The Disintegrations of Civilizations. Volume 2, an abridgement of Volumes VII-X, includes sections on Universal States, Universal churches, Heroic Ages, Contacts Between Civilizations in Space, Contacts Between Civilizations in Time, Law and Freedom in History, The Prospects of the Western Civilization, and the Conclusion.